AN ANALYSIS OF ASSERTIVE ILLOCUTIONARY ACTS USED BY LIANNA FIX IN UKRAIN WAR NEWS - Kamila Rizkya Ramadani; I.A. Putri Gita Ardiantari (ID Solutions, 2023)
This study focussed on classifying the types of assertive illocutionary used by a resource person named Lianna Fix in the news of the Ukrainian War and the meaning of the assertive illocutionary act conveyed by the resource persons in the news of the Ukrainian War. This study used a qualitative method to analyze the data descriptively by using sentences that have been arranged into paragraphsThis study also used a quantitative method to determine the frequency of the types of illocutionary assertive used by sources in the Ukraine War news. The theory proposed by Searle and Vanderveken, (1985) was applied to classify to classify the types of assertive illocutionary acts used by the resource persons in the Ukraine war news. The results of the study indicated that there are four types of assertive used by sources in the Ukraine war news: informing, stating, expressing opinions, and reminding. Based on the data, there are 18 utterances that are included in the type of assertive illocutionary acts found in the utterances of the sources in the Ukraine war news. The type of assertive illocutionary act to inform became the dominant type used by the local guide's narrative. This applies (38.89%) for 4 utterances, states (22.22%) for 3 utterances, express opinions (16.67%) for 4 utterances, and remind (22.22%) for 4 utterances.